Working Capital Management and Profitability of Agri-Food Businesses Listed in the Stock Exchange of Thailand before and after COVID-19 - Kanchanalai, Pichaya; Davivongs, Kuntonrat; Limsombunchai, Visit (Journal of Humanities and Social Sciences Thonburi University, 2024)
Working capital management is essential to a firm’s liquidity and profitability, particularly during an economic crisis. This research aims to investigate the relationship between working capital management and profitability of companies in agribusiness as well as food and beverage sectors listed on the Stock Exchange of Thailand, before and after the COVID-19 pandemic. The study uses data from quarterly financial statements of 40 listed companies from 2018 to 2022, and descriptive statistics and Pooled OLS Regression analyses. We find that working capital management is related to the net profit margin of companies in the food and beverage sector. Shortening cash conversion cycle, especially reducing average collection period and extending average payment period, can increase the net profit margin. In addition, the relaxed investment policy, and the financing policy that uses short-term borrowing to support a high proportion of current assets, lead to a higher net profit margin. Our results also show that working capital management has become even more critical to a firm’s profitability in the wake of the COVID-19 crisis.